Reversal of epigenetic age and body composition improvement in consumers of resveratrol-enriched wine - Pastor, Raul Francisco (2024)
Biological aging (BA) is a universal process involving vital function deterioration. One of the root causes of BA is epigenetic DNA hypermethylation. Epigenetic age (EA) is defined as the most important risk factor for chronic non-communicable diseases, so its modulation is an exciting emerging field of science. Although there are numerous investigations on the mechanisms of aging, today there are few studies that measure EA in humans after an intervention. The objective of this research study was to evaluate EA and body composition after the consumption of wine enriched with Resveratrol. The results showed a decrease in EA (p 0.011) and a deceleration in epigenetic age acceleration (p 0.006) after three and a half months. Also, we were able to confirm significant improvements in body composition with a 1.6 kg decrease in fat mass, (p 0.0004); and an increase in muscle mass of 300 g (p 0.019). To our knowledge, this is the first time a highly significant EA reduction has been demonstrated in consumers of resveratrol-enriched wine combined with healthy remodeling of body composition. These findings might be relevant to maintain health, increase life expectancy, and prevent the damage caused by aging. The study was registered in ClinicalTrials.gov (NCT05981053).